Factors Affecting the Use of ICT Services in Commercial Bank of Ethiopia: The Case Study of Southern Regional State in Hossana Town Branches - Solomon Abera Tirkaso; Patrick D. Cerna (Archives of Current Research International, 2016)
ICT has brought unprecedented changes and transformation to banks such as online banking, mobile banking, branch networking, automated teller machine (ATM)and Point of sale services. In Ethiopia, in particular to the government-owned Commercial Bank the lack of assistance of employee to its customers on ICT enabled-services and resistance within them hamper its slow adoption. Thus, the purpose of the study is to identify factor affecting customers and employees usage of ICT services in selected branches of commercial banks in Hossana town branches. The study employs descriptive research design and both qualitative and quantitative methods were used. Using structured questionnaires, observations and personal interview, the data were collected from 192samples which were selected by employing availability, convenient and purposive sampling techniques. In order to achieve the research objective descriptive and econometrics (ANOVA, pears correlation and multiple regression models) were employed for data analysis. The result of multiple regression model revealed that gender and marital status had no influence on the use of ICT services; there was a positive relationship between the age, education level, occupation, security concern, system quality and experiences of the respondents with the use of ICT services. The study confirmed that lack of computer literate professionals, high cost of internet, power interruption, security risk, system quality risk, poor internet connectivity, lack of ICT skilled employees and customers are a major factors that affect Information and Communication Technology services in the banks. Thus, it has been recommended that Commercial Bank of Ethiopia should give additional emphasis to reliability, responsive and transaction efficiency to increase the awareness of customers and employees to use ICT services.